Mine-scale numerical modelling, seismicity and stresses at Kiirunavaara Mine, Sweden - Vatcher, Jessica; McKinnon, Stephen D.; Sjöberg, Jonny (Luleå tekniska universitet, Geoteknologi, 2014)
LKAB’s Kiirunavaara Mine, located in northern Sweden, has exhibited seismic behaviour since the mining production extended below 700 m depth. Iron ore is mined from the 4.5 km long orebody via sublevel caving at a production rate of 28 million tonnes per annum. The deepest current production level is at approximately 800 m depth, and current mining plans call for mining to about 1200 m depth. It is thus of critical importance for LKAB to gain a deeper understanding of the stress and rock mass behaviour at the mine.The Kiirunavaara orebody has complex geometry and geology, which is represented using the discontinuum distinct element code 3DEC. As part of a larger series of models investigating the influence of strength and structural geology on rock mass behaviour, the results of multiple continuum models are presented. The goals of these continuum models included: i) obtain a better understanding of the virgin stress field and redistribution of stresses caused by mining, ii) further define the extent of mining induced plastic failure, and iii) increase the understanding of existing failure mechanisms at the mine.The elastic and plastic continuum models accurately produced principal stresses similar to measurements recently conducted at two sites in the mine, confirming the previously estimated virgin stress state. Spatial correlations between plastic failure in the model and seismicity in the hangingwall and footwall were found. However, these correlations were not consistent throughout either material for any evaluated set of material properties; either the plastic failure in the footwall or hangingwall corresponded well with seismicity. This may be because a set of rock mass properties which represent rock mass failure at this scale have not been evaluated or that some underlying failure mechanisms causing seismicity are not represented in the models, for example, failure along discontinuities. Some events larger than moment magnitude of 1.2 in the hangingwall, in particular shear source mechanisms events, do ...